Perspectives on the governance, standards, talent development, and regulation of artificial intelligence in the UK: Visit by the Malaysian delegation (13 to 16 March 2023) / Dr Azliza Mohd Ali and Assoc. Prof. Dr Shuzlina Abdul Rahman - Mohd Ali, Azliza; Abdul Rahman, Shuzlina (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
In 2021, Malaysia has published its National AI Roadmap (also known as "AI-RMAP"), which examined the development of Malaysian AI ecosystem. AI-RMAP provided suggestions for steps to realise Malaysian AI vision. In keeping with this national aspiration, selected Malaysian researchers, innovators, and government officials, through the Science and Innovation Network of the British High Commission ("BHC"), Kuala Lumpur had a working visit involving leading research centres and universities as well as key government institutions in the United Kingdom from 13 to 16 March 2023. The purpose of the visit was to promote knowledge sharing and cooperation between Malaysia and the UK in relation to the advancement of artificial intelligence ("AI") technologies. Through this trip, the UK hoped to introduce key players and AI initiative & technologies to Malaysia's delegation from the Ministry of Science, Technology, and Innovation and the AI Consortium, a networking organisation for Malaysian AI researchers. By collaborating with top-tier AI institutions in the UK, the visit has the aim of fostering AI research, innovation, and development in Malaysia. As stated in the Strategic Initiative 1.4 of Malaysia's National AI Roadmap, the members of the delegation also seek to address concerns in relation to the governance, standards, and legislations applicable for the use of AI technologies. This will entail locating possible UK advisors and creating plans to guarantee efficient AI governance. This initiative will be coordinated by Universiti Teknologi Malaysia (UTM).